A standard for the form of a line is the slope-intercept form:
y = mx + b
where m is the slope of the line and b is the y-intercept: the point (0, b).
For the first problem we have a slope of:
m = (4/3 - 0)/(0 - 3/4) = (4/3)/(-3/4) = -16/9
So we know that the line is of the form:
y = -(16/9)x + b
Consider our first point on this line: (3/4, 0). Inserting this point into our line equation gives us:
0 = -(16/9)(3/4) + b
Solving for b:
0 = -(4/3) + b
b = 4/3
Thus the line is
y = -(16/9)x + (4/3)
You do the second one. I get that y = -(10/33)x + (24/11)
-Dan